Computer-aided measurements of wheelchair basketball players displacements: Guidelines for training modelization - Pérez, J.; Refoyo, I.; Navarro, E.; Sampedro, J. (International Journal of Computer Science in Sport, 2002)
In team sports, like wheelchair basketball (WB), it is necessary to evaluate displacements performed (distance travelled, intensity, velocity, accelerations, etc.), to define exigency profile and to find accurate training guidances for training modelization.